O papel mediador do apoio social na relação entre sintomas depressivos e risco suicida em universitários na perspectiva do sexo - Carrijo, Marcos Vítor Naves (2023)
ABSTRACT: Objective: To analyze the mediating role of social support in the relationship between depressive symptoms and suicidal risk in university students from the perspective of gender. Method: analytical cross-sectional study, carried out at the Federal University of Mato Grosso (UFMT), with 1026 university students, from September to November 2020. Online data collection took place via the REDCap platform, using the following instruments: self-completion questionnaire divided into sections with sociodemographic and academic characteristics; module C of the Mini International Neuropsychiatric Interview (MINI), which investigated the presence of risk in the last 30 days; Patient Health Questionnaire-9 (PHQ-9), which examined the presence of depressive symptoms, and the Social Support Scale (SSS), which assessed the perception of social support. Data analysis was performed using the Statistical Package for Social Sciences (SPSS), version 27.0 and for the risk of suicide and depressive symptoms, descriptive analyzes were used using absolute and relative frequencies. Association tests were used to compare differences between depressive symptoms and perceived social support and aggregated according to sex and suicide risk status. Correlational analysis was performed using Pearson's r coefficient to verify the magnitude of associations between continuous variables, Fisher's transformation test, which verified the differences in the magnitude of correlations between the two groups, and simple mediation analysis using the PROCESS macro. The study was approved by the Health Research Ethics Committee of the Federal University of Mato Grosso. Results: the findings show a predominance of females (82.0%), heterosexuals (98.0%), had no income (22.0%), no partner (54.0%), selfdeclared white (60.0%), who have some religious belief or practice (66.0%). The mean depressive symptomatology was 11.97 (SD ±6.79) for those who did not present a risk of suicide, 19.71 (SD ±6.39) for those who presented a risk and a prevalence of 48% risk of suicide. There was a positive correlation between suicide risk and depressive symptoms and a negative correlation between suicide risk and social support among students. The mediation analysis showed a mediator effect of 14.8% in the relationship between depressive symptoms and suicidal risk in the female audience, and this mediation was not observed in the group of male students. Conclusions: identifying the mediation of social support can help in reflection for the elaboration of equitable actions aimed at preventing and reducing the risk of suicide in university students.